Ходосівський археологічний комплекс: вивчення, охорона, експериментальне моделювання - Готун, І.А.; Казимір, О.М. (Археологія і давня історія України, 2010)
Публікація характеризує втілювану Північною експедицією ІА НАНУ комплексну програму дослідження, охорони, музеєфікації, студіювання експериментальної археології на низці пам’яток південних київських передмість поблизу с. Ходосівка Києво-Святошинського р-ну. В южных пригородах Киева, вокруг с. Ходосовка сосредоточено свыше 30 памятников культурного наследия, датирующихся мезолитом — новым и новейшим временем. В их числе — многослойное поселение между Ходосовкой и Лесниками со специфическим древнерусским селищем в составе и поселение древнерусского и монгольско-литовского времени Ходосовка-Рославское с многоструктурной экономикой, богатым вещевым материалом, мастерской по обработке янтаря. Северной экспедицией Института археологии НАН Украины, исследующей комплекс, реализуется программа изучения и охраны памятников, экспериментальной археологии (гончарство, лесохимические промыслы, черная металлургия, домостроительство и др.), музеефикации комплекса и популяризации культурного наследия. In the Southern suburbs of Kiev, around Khodosivka village it is concentrated over 30 monuments of a cultural heritage dated New and Newest time of Mesolithic Age. Among them are a multilayered settlement between Khodosivka and Lisnyky with a specific Old Russian settlement in structure and a settlement of Old Russian and Mongol-Lithuanian time Khodosivka- Roslavsky with the multistructural economy, a rich ware material and a workshop on amber processing. The Northern Expedition of the Ukrainian Academy of Science’s Institute of Archaeology investigates the complex and realizes the program of studying and protection of monuments, experimental archeology (pottery, timber-chemical crafts, ferrous metallurgy, house-building, etc.), museum making in the complex and popularization of cultural heritage.